The bridegroom - Miller, Linda Lael (Miller, Linda Lael. Stone Creek novel, 2014)
Undercover agent Gideon Yarbro is renowned for stopping outlaws almost before they commit a crime. But now he must stop a wedding--despite the bride's resistance. Lydia Fairmont will lose everything if she doesn't honor her betrothal to a heartless banker. Unless she marries someone else instead ... whether it's a love match or not. Determined to honor his own decade-old promise to help Lydia, Gideon carries her off to Stone Creek and makes her his reluctant wife. Forget a honeymoon for "show"--Not with a vengeful ex-fiance on their trail and a hired gun on the loose. But there just might be hope for the marriage ... and two hearts meant for each other.